PENDAMPINGAN ECOPRINT SEBAGAI POTENSI DESA GONDANG - Shafa Jasmine Salsabila; Daffa Kharisma Aulia; Adela Wafiq Azizah; Fenty Nur Qorimah; Leni Ratnawati; Achmad Amirul Khaqqi; M. Fahmi Afrijal; M. Fadel Ramadhan; Deeky Framudya; Muhammad Yasin (Prosiding Patriot Mengabdi, 2023)
Batik assistance to villages is a program or initiative that aims to provide assistance, guidance and assistance to villages in the development of the batik industry. This assistance is carried out to increase the economic and cultural potential of the village through the development of a batik business. Batik mentoring programs can involve various aspects, such as batik skills training for village communities, assistance with batik equipment and raw materials, introduction to more modern batik techniques, and guidance in terms of batik production and marketing management. Through this assistance, villages can develop skills in making batik, improve the quality of batik products, and expand market reach. In addition, batik assistance also has the potential to create new jobs, increase the income of rural communities, and preserve the cultural heritage of batik. Batik assistance to villages can have a positive impact, including improving the standard of living of village communities, reducing poverty, increasing economic independence, and strengthening the cultural identity of village communities. In addition, batik assistance can also be a model or example for other villages in efforts to develop creative industries and preserve local culture. Ecoprint has great potential in producing creative products with added value developing skills in ecoprint techniques, including the selection of raw materials, printing processes and product finishing. In addition, they also learn about marketing and business management. Ecoprint assistance has encouraged the creation of new jobs and increased income for the people of Gondang village. The results of this research are expected to contribute to the development of local economic potential and the empowerment of rural communities in Indonesia, particularly in the arts and crafts sector.